PENYULUHAN DAN PELATIHAN PENGOLAHAN SABUT KELAPA - Tuasikal M. Amin (Asian Journal of Innovation and Entrepreneurship, 2015)
Coconut (Cocos nucifera) is the sole member of the clan of the tribe palmCocos-arenan or Arecaceae. This plant is used almost all parts by humans that is considered as a versatile plant, especially for coastal people. With such conditions, it isunfortunate people at Desa Kebonharjo, Kecamatan Samigaluh, Special Region ofYogyakarta yet have insight into the coco fiber processing. Often, coconut only considered as waste that can not be used. Therefore, the authors initiated counselingand training held coco fiber processing. With hope, which was originally unused wastecan be processed into goods more useful. Furthermore, the processed results can be used as a commodity trading high profit.